2017
DOI: 10.1590/1982-0194201700021
|View full text |Cite
|
Sign up to set email alerts
|

Ambiente da prática, satisfação e clima de segurança: percepção dos enfermeiros

Abstract: Objective: To assess the nurses' perception on the practice, job satisfaction, safety climate and to verify correlations among these variables and the adequacy of material and human resources, as well as the intention to stay at the institution and in the profession. Methods: A descriptive study with a quantitative approach was undertaken. To calculate the sample, a p-coefficient of 0.50 was considered, assuming a 3% sampling error and a 5% significance level, which resulted in 1057 subjects. For the data coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 20 publications
(22 reference statements)
4
21
1
10
Order By: Relevance
“…Most professionals (69.2%) did not have any other registered job, corroborating other results findings (11,(13)(14) . However, a study conducted in a private hospital in Minas Gerais found that 53.66% of professionals who participated had another registered job, but there was not a significant relation between this fact and the score regarding the atmosphere of safety (10) .…”
Section: Discussionsupporting
confidence: 89%
“…Most professionals (69.2%) did not have any other registered job, corroborating other results findings (11,(13)(14) . However, a study conducted in a private hospital in Minas Gerais found that 53.66% of professionals who participated had another registered job, but there was not a significant relation between this fact and the score regarding the atmosphere of safety (10) .…”
Section: Discussionsupporting
confidence: 89%
“…Establishing positive PE in clinical settings is of paramount importance for patient safety and nurses’ overall wellbeing. In this study, nurses perceived their PE as moderate, which is similar to the results of studies conducted in Iran and China but slightly lower than those conducted in Brazil and previously conducted in the Philippines . Nurses from various countries are likely to have different views on PE and different cultural backgrounds in providing care .…”
Section: Discussionmentioning
confidence: 99%
“…Porém, ao se pontuar a relação da carga de trabalho com o clima de segurança, constata-se um grande gap de conhecimento no país, pois os estudos normalmente se voltam à investigação da cultura de segurança do paciente (12) . Outras pesquisas recentes relacionam o clima de segurança com características do trabalho da enfermagem (13) , ambiente de prática e satisfação no trabalho (14) , o que reforça a incipiência de conhecimento da relação do clima de segurança com a carga de trabalho da equipe de enfermagem.…”
Section: Introdução Métodounclassified